Primary School Storytelling Skills Based on Local Wisdom - Sudrajat, Wini Sopiantini; Sujana, Atep; Sopandi, Wahyu; Rahman, Rahman (International Conference on Elementary Education, 2020)
The purpose of this study is to describe storytelling skills in fourth-grade children of SDN Pasanggrahan 3, Sumedang Region, based on local wisdom. Story-telling skills explain stories that exist in the Sumedang area. The research method used a descriptive qualitative nature. A research tool provided in the form of observation for students and teachers during the training took place, and interviews were conducted before and after the training. The subjects of this study were 33 fourth-grade students, consisting of 18 students and 15 students, who, as a rule, were 9 years old. The results of the data analysis showed that: (1) based on the results of the survey, 90% of students answered that the storytelling approach is based on local wisdom, interesting; (2) in addition to the ability to read a story, students can understand reading and retell reading in their own language; (3) living conditions and class overcrowding; (4) students are motivated to search or research stories in their field